2016
DOI: 10.1021/acscatal.6b02203
|View full text |Cite
|
Sign up to set email alerts
|

Metallic NiPS3@NiOOH Core–Shell Heterostructures as Highly Efficient and Stable Electrocatalyst for the Oxygen Evolution Reaction

Abstract: We report metallic NiPS 3 @NiOOH core−shell heterostructures as an efficient and durable electrocatalyst for the oxygen evolution reaction, exhibiting a low onset potential of 1.48 V (vs RHE) and stable performance for over 160 h. The atomically thin NiPS 3 nanosheets are obtained by exfoliation of bulk NiPS 3 in the presence of an ionic surfactant. The OER mechanism was studied by a combination of SECM, in situ Raman spectroscopy, SEM, and XPS measurements, which enabled direct observation of the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
179
0
6

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(200 citation statements)
references
References 55 publications
(113 reference statements)
10
179
0
6
Order By: Relevance
“…Enhanced catalytic activity is due to the higher ionic strength of OHÀ ions and associated ionic conductivity dependence which is evidenced from the lower R ct value in the EIS studies shown in Figure S10 in the ESI. [5,35,40,41,68,75,76] To support and study the insightfulness of OER on Ni MOF in alkaline medium it was further examined. Figure S11 and S12 show the summary of these results.…”
Section: Physical and Chemical Characterizationsmentioning
confidence: 99%
“…Enhanced catalytic activity is due to the higher ionic strength of OHÀ ions and associated ionic conductivity dependence which is evidenced from the lower R ct value in the EIS studies shown in Figure S10 in the ESI. [5,35,40,41,68,75,76] To support and study the insightfulness of OER on Ni MOF in alkaline medium it was further examined. Figure S11 and S12 show the summary of these results.…”
Section: Physical and Chemical Characterizationsmentioning
confidence: 99%
“…Recently, transition-metal phosphides have also been demonstrated as efficient electrocatalysts for HER in an alkaline medium,8h,8i,13 besides their high HER catalytic activity in acidic media 8a,8d,8g,14. In addition, it has been demonstrated that bimetallic phosphide NiCoP displays higher HER activity than monometallic phosphide Ni 2 P, due to its optimized H binding energy of nearly zero (close to that of Pt) on the surface of NiCoP, which is beneficial for the reversible adsorption and desorption of H 13 a .…”
Section: Introductionmentioning
confidence: 99%
“…Der Degradationsgrad kann vom verwendeten Medium abhängen. [21,22,37,40,42,43,45,47,65,67,68] In Analogie zur HER hat MPSe 3 -Volumenmaterial ein geringeres Onset-Potential als MPS n ,j edoch sind die Ausbeuten bei weitem nicht konkurrenzfähig,u nd die Stabilitäti st sehr mangelhaft. Die XPS-Untersuchung des BiPS 4 -Materials zeigte eine vollständige ¾nderung seiner Zusammensetzung unter Komplettverlust des P. [21] Die MPSe 3 -Materialien waren in alkalischen Medien weniger stabil als in sauren, wobei FePSe 3 und MnPSe 3 jedoch den anderen Verbindungen überlegen waren und deshalb als die beiden interessantesten Vertreter der untersuchten Reihe gelten (Abbildung 4i,j).…”
Section: Elektrochemische Energieumwandlungunclassified
“…[22] Wiew eiter oben in Abschnitt 4e rwähnt, bestehen noch weitere Herausforderungen im Zusammenhang mit der OER, der anodischen Halbreaktion der Wasserelektrolyse. [45] Abbildung 5. a) SEM-Bild eines exfolierten NiPS 3 -Nanoblatts. [56] Viele Studien haben gezeigt, dass die aktiven Zentren der OER-Katalysatoren heterogene Reaktionsintermediate sind, und für Übergangsmetallkatalysatoren wurden die Spezies M-OH, M=Ou nd M-OOH detektiert.…”
Section: Elektrochemische Energieumwandlungunclassified
See 1 more Smart Citation